Authentic Assessment Research Trends in Biology Learning: A Bibliometric Analysis - Mutiara Lubis; Yus Mochamad Cholily; Abdulkadir Rahardjanto; Yuni Pantiwati; Poncojari Wahyono (Al Jahiz, 2025)
Authentic assessment holds a crucial role in modern biology education as it supports competency-based evaluations that enable students to apply scientific knowledge in real-world settings. This study presents a bibliometric analysis of research trends on authentic assessment in biology learning using data from the Scopus database. Employing a quantitative approach, the study analyzed the temporal distribution, international collaboration, dominant keywords, and thematic evolution from 39 selected articles through tools such as co-authorship network analysis, keyword co-occurrence mapping, and thematic evolution analysis. Results indicated a significant rise in publications since 2018, peaking during the COVID-19 pandemic due to shifts in assessment methods for online learning. The disciplinary distribution showed a predominance of social sciences (26.1%) intersecting with biology and environmental science. The United States and the UK emerged as leading contributors, with support from institutions like the National Science Foundation. Keyword analysis identified two major clusters: animal-based assessment (motor theme) and molecular biology (emerging theme). However, the literature showed limited representation from developing countries and minimal exploration of advanced technologies. This study contributes by (1) mapping scientific developments in authentic assessment research, (2) offering a bibliometric analysis protocol applicable to similar areas, and (3) suggesting future directions including global collaboration, validation of long-term instruments, and focus on niche topics like biodiversity-based assessments. The findings offer practical implications for designing context-responsive assessment guidelines. Nonetheless, the study is constrained by its reliance on Scopus and English-language sources, potentially excluding other relevant contributions.